Application of Lattice-Boltzmann Method for Analysing Detachment of Micron-Sized Particles from Carrier Particles in Turbulent Flows - Cui, Yan; Sommerfeld, Martin (Flow Turbulence and Combustion, 2018)
Numerical calculations based on the Lattice-Boltzmann method were performed for a particle cluster consisting of a large spherical carrier particle covered with hundreds of small spherical drug particles. This cluster, fixed in space within a cubic computational domain, was exposed to turbulent plug airflow with predefined intensity. Such a situation is found in dry powder inhalers where carrier particles blended with fine drug powder are dispersed in a highly turbulent flow with the objective of detaching the drug powder for pulmonary delivery. Turbulence was generated by a digital filtering technique applied to the inflow velocity boundary condition. This technique was first validated by analysing the turbulence intensity at 15 fluid nodes along the stream-wise direction of the computational domain. The size ratio between the drug and carrier particle was 5 μ m/100 μ m, and the coverage degree of the carrier by the small particles was 50%, which is a typical value for carrier particle blending. The range of carrier particle Reynolds numbers considered was between 80 and 200, typical values found in inhaler devices. Exemplarily, at Re = 200 turbulence intensity was varied from 0.3% to 9.0%. The systematic increase of the mean flow (i.e. 80 < Re <200) resulted in varying turbulence intensities from 20 to 9%. These simulations provided the temporal evolution of the fluid dynamic forces on the drug particles in dependence of their angular position on the carrier in order to estimate the possibility of drug particle detachment. For turbulent conditions (i.e. Re = 200 and I = 9.0%) the maximum fluid forces on the drug particles were found to be about 10-times larger than found in laminar flow. The fluctuations in the forces were found to be higher than the flow velocity fluctuations due to the modification of the boundary layer around the cluster and instabilities triggered by the turbulent flow. There are three possibilities for detaching the drug powder, namely, through lift-off and sliding or rolling. Lift-off was found to be of minor importance due to the observed small normal fluid forces even at Re = 200 and I = 9.0%. The probability of sliding and rolling detachment in dependence of the angular position was estimated based on measured adhesion properties, i.e. van der Waals force, adhesion surface energy and friction coefficient. The remarkable rise of detachment probability for both effects due to the action of turbulence is an important finding of this study. In accordance with laminar flow, rolling detachment occurs before sliding, however in turbulent conditions over the entire carrier particle. The present studies improve the understanding of drug particle detachment from carrier particles in an inhaler device. The results will be the basis for developing Lagrangian detachment models that eventually should allow the optimisation of dry powder inhalators through computational fluid dynamics.<br
Keywords: Turbulent flow; Fully resolved particle cluster; Lattice-Boltzmann method; Drug powder detachment; Detachment probabilities; Fluid dynamic forces; Dry powder inhaler